2014
DOI: 10.1371/journal.pone.0094612
|View full text |Cite
|
Sign up to set email alerts
|

IKAP Deficiency in an FD Mouse Model and in Oligodendrocyte Precursor Cells Results in Downregulation of Genes Involved in Oligodendrocyte Differentiation and Myelin Formation

Abstract: The splice site mutation in the IKBKAP gene coding for IKAP protein leads to the tissue-specific skipping of exon 20, with concomitant reduction in IKAP protein production. This causes the neurodevelopmental, autosomal-recessive genetic disorder - Familial Dysautonomia (FD). The molecular hallmark of FD is the severe reduction of IKAP protein in the nervous system that is believed to be the main reason for the devastating symptoms of this disease. Our recent studies showed that in the brain of two FD patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…We next examined whether the lack of IKAP alters expression levels of several genes known to be affected in FD patients and other FD mouse models [24,30,40,41,61]. RNA was extracted from the brains and DRGs of 3-month-old CKO Tyrp2 FD mice and control littermates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next examined whether the lack of IKAP alters expression levels of several genes known to be affected in FD patients and other FD mouse models [24,30,40,41,61]. RNA was extracted from the brains and DRGs of 3-month-old CKO Tyrp2 FD mice and control littermates.…”
Section: Resultsmentioning
confidence: 99%
“…As IKAP co-localizes and purifies with cytoplasmic proteins [3032], it has been suggested that IKAP functions in tRNA modification [3335], exocytosis [36], cell adhesion and migration, microtubule organization [20,32,37,38], p53 activation [39], and c-Jun N-terminal kinase (JNK) signaling pathway regulation [19,23,31]. Recent studies focused on IKAP function in neurons suggest that IKAP influences oligodendrocyte differentiation and myelin formation [40,41], is crucial for vascular and peripheral neural development during embryogenesis [20,42,43], regulates NGF signaling, and distributes target innervations [19,20]. Deletion of IKAP in migrating neural crest further documented a key role for IKAP in DRG progenitors for correct timing of neurogenesis and survival of TrkA + nociceptors and thermoreceptors [44].…”
Section: Introductionmentioning
confidence: 99%
“…As it turns out, both Ikbkap flox/flox and Ikbkap Δ 20/flox mice recapitulate several of FD major phenotypic features, including reduced IKAP expression, intrauterine growth retardation, reduced birth weight, failure to thrive, reduced number of fungiform papillae on the tongue, progressive ataxia, kyphosis, stress-induced seizures, decreased temperature perception and impaired development and maintenance of sensory and sympathetic neurons (Figure 4 and Table 1; Dietrich et al , 2012). Similar to FD patients, these FD mouse models also display reduction of expression of genes and proteins involved in myelination in the CNS (Cheishvili et al , 2014a). …”
Section: Animal Models For Fdmentioning
confidence: 99%
“…Coincident with the dual roles of Elongator in transcriptional and translational regulation, it has been shown that several genes involved in cell migration and a few meiotic genes during spermatogenesis were down-regulated in FD-derived fibroblasts (23) and in mouse upon Elp1 depletion (22), respectively, and that several genes involved in oligodendrocyte development and myelin formation were down-regulated both in the cerebrum of FD patients (24) and in an FD mouse model (25). Recently, Frances Lefcort and coworkers discovered that Elp1 is essential for the genesis of tropomyosinrelated kinase A nociceptors and thermoreceptors in mice (26).…”
mentioning
confidence: 98%